PENGARUH PERTUMBUHAN LABA DAN INVESTMENT OPPORTUNITY SET TERHADAP KUALITAS LABA (STUDI PERUSAHAAN SEKTOR JASA YANG TERDAFTAR DI BEI TAHUN 2018) - Muhammad Faisal Arif (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2020)
This study aims to determine whether profit growth and investment opportunity sets on earnings quality in the Trading Services sector companies listed on the Indonesia Stock Exchange. Data collection uses secondary data obtained from financial statements using purposive sampling techniques. The population is the Trade Sector Services Company listed on the Indonesia Stock Exchange in 2018 for a total of 167 observations. While the samples taken amounted to 59 observations. The results of the research variable data have been tested for classical assumptions in the form of normality assumptions, multicollinearity assumptions and heteroscedasticity assumptions. The method of data analysis uses multiple linear regression techniques.The results of the research partially show that Profit Growth has a positive effect on earnings quality, while the Investment Opportunity Set has no effect on Profit Quality.